Nitrous oxide emissions from grass–clover swards as influenced by sward age and biological nitrogen fixation. (6th August 2020) - Reinsch, Thorsten; Malisch, Carsten; Loges, Ralf; Taube, Friedhelm
Abstract: Grassland renovation by cultivation and reseeding has been shown to increase short‐term emissions of N2 O, but there is uncertainty about long‐term effects, despite the potential impacts of reseeding on sward composition and soil functions. A field experiment was therefore carried out to determine how N2 O emissions from previously renovated grasslands varied in the intermediate to long‐term, compared with an undisturbed permanent grassland (PG). Plots on the PG site were renovated, either two (G2) or five (G5) years prior to the two experimental years. In each sward age and experimental year, annual N2 O‐measurements were conducted on a weekly basis and compared with the undisturbed PG. Plots were either unfertilized or were fertilized with slurry (240 kg N ha −1  year −1 ). On average, annual N2 O emissions were 0.39 kg N/ha for the unfertilized swards, and 0.91 kg N/ha for slurry‐fertilized swards. Sward age had no effect on N2 O emissions. With increasing sward age the proportion of legumes in the sward was reduced, but a minimum biological nitrogen fixation (BNF) of 88 kg N/ha was maintained even in the fertilized PG. Both sward age and BNF were of limited importance for the annual N2 O emissions compared with the effects of soil carbon content and nitrogen surplus levels. However, measured N2 O emissions were low in all sward age treatments, with a low risk of additional N2 O emissions when BNF is taken into account in fertilizer planning.